Pediatric Diabetes Technology Management: An Italian Exploratory Study on Its Representations by Psychologists and Diabetologists - Annamaria Tupputi; Lucia Giardinieri; Silvia Monaco; Michela Di Trani (MDPI AG, 2023)
The incidence of type 1 diabetes (T1D) has increased by about 3% per year over the last two decades. Continuous Insulin Subcutaneous Therapy (CSII) is widely used in the pediatric population with diabetes; however, it requires more preparation by the treating team and a careful selection of its potential users. Prescriptive provisions vary from region to region, and the perspective of health workers in this regard remains an unexplored area. The aim of this research project is to explore the representations of a group of diabetologists and psychologists working in pediatric diabetology throughout the country, regarding their roles, functions, and activities as part of a multidisciplinary team; it also aims to investigate their views on the potential benefits of CSII and the types of individuals who apply for the use of this technology. A socio-anagraphic data sheet was administered, and two homogeneous focus groups were conducted, one for each profession, which were then audio recorded. The transcripts produced were analyzed using the Emotional Text Mining (ETM) methodology. Each of the two corpora generated three clusters and two factors. For diabetologists, a focus on patient care emerged at different levels, involving collaboration with other health professionals and engagement with the community, often incorporating technology in medical interventions. Similarly, psychologists' representations highlighted interdisciplinary networking with a stronger emphasis on the psychological processes involved in managing the disease, from acceptance to the elaboration and integration of diabetes into the family narrative. Understanding the representations of health professionals working in pediatric diabetes with new technologies can contribute to the consolidation of a network of professionals through targeted work on possible critical issues that may arise.